The Effectiveness of the Implementation of the Case Methods in the Learning Evaluation Course at State Islamic University of North Sumatera - Ananda, Rusydi (SCAD Independent, 2018)
In the development of learning, it is very important to consider the characteristics of students to choose the appropriate approach in the learning activities. Teaching staff as the organizer of learning activities are required to seek the interaction of learners with other components of the learning system optimally. This research reveals about the efforts to improve student learning outcomes in the course by applying case study method strategy. The selection and application of learning strategy of the case method in learning course and learning Evaluation is conducted in accordance with the characteristics of the Learning Evaluation course itself which requires thinking skills and interaction skills from the students to understand the materials contained therein. The method used in this research is classroom action research. The results showed that the implementation of case study method strategy can improve learning outcomes in the course of Evaluation of Learning. This is evident from the increasing percentage of students in the eight aspects observed from both cycles carried out in the action of this study. This fact is supported by the result of t test statistic test where obtained tct = 7,17 while ttable price = 1,682 so it can be interpreted that applying of case study method strategy can improve learning result of learning course lesson.